2021
DOI: 10.1097/bpo.0000000000001836
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of MPFL Reconstruction Utilizing a Quadriceps Turndown Technique in the Adolescent/Pediatric Population

Abstract: Purpose: Recurrent instability following a lateral patellar dislocation is a common indication for surgical intervention. Several surgical procedures are described in the literature to address recurrent patellar instability. Medial patellofemoral ligament (MPFL) reconstruction utilizing the quadriceps turndown technique attempts to restore medial stability. Results of the quadriceps turndown technique have previously only been reported in adult populations. The purpose of this study was to assess the safety, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(83 reference statements)
2
3
0
Order By: Relevance
“…Of the patients, 87% returned to the same level of sport as preoperatively, while 27% had to reduce their level of sport following MPFL reconstruction. These findings confirm the results of Fisher et al, who used a quadriceps turndown technique with 94% of patients returning to a pre-injury level of sport [ 49 ]. Liu et al found, in a retrospective study, that 94.5% of patients were able to return to sport at one year, with only 74% returning to the same level of play [ 50 ], with similar results found by Nelitz et al [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…Of the patients, 87% returned to the same level of sport as preoperatively, while 27% had to reduce their level of sport following MPFL reconstruction. These findings confirm the results of Fisher et al, who used a quadriceps turndown technique with 94% of patients returning to a pre-injury level of sport [ 49 ]. Liu et al found, in a retrospective study, that 94.5% of patients were able to return to sport at one year, with only 74% returning to the same level of play [ 50 ], with similar results found by Nelitz et al [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…The last follow-up scores were 86.23 ± 7.71 versus 88.37 ± 3.71 at a 46.5 ± 20.9 months follow-up, respectively. These results agree with the findings of the present systematic review and are further supported by additional studies which have not been included because, though published in peer-reviewed journals, they did not meet our strict inclusion criteria [19,[39][40][41][42][43][44][45][46][47][48][49][50][51]. On the other hand, the complication profile of hardware-free fixation shares similarities with implantbased fixation techniques, including subjective instability, positive apprehension test, and redislocation [55].…”
Section: Discussionsupporting
confidence: 88%
“…Titles and abstracts were independently screened, and 27 articles were selected for full-text evaluation. Seven studies were excluded because of insufficient followup [19,[39][40][41][42][43][44] and seven more because Kujala Anterior Knee Pain Scale was not used or data were insufficient to evaluate post-surgical improvement [45][46][47][48][49][50][51]. Finally, eight studies met the predetermined eligibility criteria, and no additional studies were included after citation screening in the systematic review (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The quads-turndown technique can be an alternative for smaller knees. 18 For tibial tubercle osteotomies, the use of headless screws buried beneath the bone cortex decreases irritation upon returning to martial arts. For selected skeletally immature patients, a medial patellar tendon transfer 19 or Roux-Goldthwait procedure can be considered.…”
Section: Orthopaedic Injuries In Martial Artsmentioning
confidence: 99%